Preliminary reduction of chromium ore using Si sludge generated in silicon wafer manufacturing process - Woo-Gwang Jung; Gu-Seul Back; Jong-Ho Kim; Young-Chul Chang; Sun-Joon Yoo (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
A basic study was performed on the preliminary reduction reaction between chromium ore and the Si sludge, comprised of SiC and Si particles, which is recovered from the Si wafer manufacturing process for the semiconductor and solar cell industries. Compacts were first made by mixing chromium ore, Si sludge, and some binders in the designed mixing ratios and were then treated at different temperatures in the 1116 °C–1388 °C range in an ambient atmosphere. Cordierite and SiO2 were confirmed to be formed in the products after the reduction. Additionally, metal particles were observed in the product with Fe, Cr, and Si components. It is found that temperatures above 1300 °C are necessary for the reduction of the chromium ore by the Si sludge. The reduction ratio for Fe was evaluated quantitatively for our experimental conditions, and the proper mixing ratio was suggested for the pre-reduction of the chromium ore by the Si sludge. This study provides basic information for the production of ferrochrome alloys on the pre-reduction of chromium ore using Si sludge.